ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENGUNGKAPAN LKPD DI PEMERINTAH KABUPATEN-KOTA DI PROVINSI PAPUA - Sria Kogoya; Agustinus Salle; Anthonius H.C Wijaya (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2019)
The population in this study is regencies / cities in the Papua Province during the last three years, namely the 2015-2017 budget year, the data obtained is the LHP data that has been audited by theBPK. the sample used in all of these studies as many as 87 samples of local government financial reports are all existing populations in the sample. The data analysis method used in this study uses multiple linear regression analysis with the SPSS 16 program. This data is processed from June to the beginning of the 2019 julli in Jayapura City, Papua Province. The results in this study indicate that the age of the Regional Government has a positive effect on the level of disclosure of regional financial statements (LKPD). and on the Local Government Size, the Number of OPD, and also the Dependency Rate have a positive and insignificant effect on the level of disclosure while the auditfindings themselves influence the level of disclosure of the LKPD.